“THE MAN CAN USE THAT POWER”, “SHE GOT COURAGE” AND “INIMBA”: DISCURSIVE RESOURCES IN COUNSELLORS’ TALK OF INTIMATE PARTNER VIOLENCE: IMPLICATIONS FOR PRACTICE - Fleischack, Annie; Macleod, Catriona Ida; Bohmke, Werner (Social Work/Maatskaplike Werk, 2017)
Given the high rate of intimate partner violence (IPV), understanding how counsellors talk about IPV and their interventions is important. The authors conducted narrative interviews with eight counsellors from non-governmental organisations (NGOs) working with IPV. Using narrative-discursive methodology, this qualitative study paid attention to the discursive resources that the participants drew upon. Two broad clusters of discursive resources and one contradictory (‘nurturing femininity’) discourse emerged. The first cluster engenders a sense of helplessness in the face of overwhelming power relations; the second enables the counsellors to foresee positive outcomes for their counselling. Implications for counselling include emphasising enabling discourses, highlighting multiplicities of gender, and wider-scale interventions.